Expressions of vascular endothelial cadherin and soluble Fas ligand in patients with viral myocarditis and their correlations - Hu Hongmei; Wang Xuejiao; Li Na; Lu Fue; Li Rui (Romanian Journal of Laboratory Medicine)
We aimed to explore the expressions of vascular endothelial cadherin (VE-cadherin) and soluble Fas ligand (sFasL) in patients suffering from viral myocarditis (VMC), and the correlations between them.